2004
DOI: 10.1016/j.jpainsymman.2003.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Equipping medical students to manage cancer pain: A comparison of three educational methods

Abstract: A Cancer Pain Structured Clinical Instruction Module (SCIM), with skills stations incorporating actual cancer patients, has been developed to enhance cancer pain education among our medical students. The Cancer Pain SCIM has not been compared with more traditional cancer pain education, thus the purpose of this study was to assess the effectiveness and durability of three educational methods for teaching cancer pain management to medical students compared with a control group. Four consecutive rotations of 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…In addition, our previous research with the 2-hour structured teaching format has consistently demonstrated its superiority over more traditional methods of instruction. 16 For example, Sloan et al 16 demonstrated that senior medical students who received a 2-hour structured education on cancer-pain management significantly outperformed students who received traditional instruction and tested with a cancer-pain OSCE at 4 months after instruction. They concluded that the SCIM format of teaching substantially improved the quality of cancer-pain education and showed durability at 4 months after instruction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our previous research with the 2-hour structured teaching format has consistently demonstrated its superiority over more traditional methods of instruction. 16 For example, Sloan et al 16 demonstrated that senior medical students who received a 2-hour structured education on cancer-pain management significantly outperformed students who received traditional instruction and tested with a cancer-pain OSCE at 4 months after instruction. They concluded that the SCIM format of teaching substantially improved the quality of cancer-pain education and showed durability at 4 months after instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported knowledge may be sufficient but the students may be not able to implement their knowledge to clinical practice. The students should learn from tests and receive feedback on which to build their knowledge and skills (Sloan et al, 2004;Mavis et al, 2002;Wass et al, 2001). On the other hand, the assessment drives learning (Wass et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The current medical education in pain evaluation and management does not provide physicians with the skills that are needed in the clinical practice (Turner and Weiner, 2002). According to previous studies (Turner and Weiner, 2002;Pö yhiä and Kalso, 1999;Watt-Watson et al, 2003;Sloan et al, 2004;Pö yhiä et al, 2005) teaching of pain related topics in the medical schools is fragmented, important topics are poorly covered and specific curricula for pain are uncommon. This is surprising, as the International Association for the Study of Pain (IASP) published a core curriculum on pain for the international needs of medical schools already over 15 years ago (Pilowsky, 1988).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 They have been used in the teaching of pain management, cancer care, and surgical techniques and have been evaluated as an effective, sustainable tool delivering durable skills and knowledge improvements. [9][10][11][12] To date, this literature has focused on the use of SCIMs to teach various aspects of a single topic. The SCIM program developed for the palliative care attachment is novel, as it covered numerous aspects of knowledge and skills essential for end-of-life care.…”
Section: Description Of the Scim Workhopmentioning
confidence: 99%